Governement, Development, Border The Significant Role of The Governement in Entikong's Border Development in Joko Widodo's Regime - Triesanto Romulo Simanjuntak (Cakrawala Jurnal Penelitian Sosial, 2018)
The border area is an important area when it includes bilateral relations between one country and another. The bilateral relationship between Indonesia and Malaysia is a relationship that always experiences ups and downs. The presidential model of Indonesia which determines the approaches of development in Indonesia, especially in border areas. Not many Presidents have touched development in the border region. Joko Widodo as the 7th President of Indonesia made a program that wants to bring the government to the entire archipelago. This makes the border area experience strengthening not only on cross-border border posts (PLBN) but also around border areas. This study uses a qualitative research model with a method of extracting data with a model of in depth interviews with residents around the border. The theory used in this study is neoclassical theory, where the activities of individuals and groups (communities) require the role of the state to improve the satisfaction desired by the individual. So that there is no exception for the presence of countries in the border region to be able to increase the level of satisfaction of the people in the border area that had not been noticed by previous Indonesian presidents.